Bureaucratic Transformation Through Digital Governance: The Experience of Surabaya City Government - Indra Prayoga; Amanda Putri Nazrullah (Asian Digital Governance Problems, 2025)
Purpose: This study analyzes the bureaucratic transformation of the Surabaya City Government through digital governance, focusing on how digital initiatives enhance efficiency, transparency, and public service innovation while addressing challenges in institutional adaptation and citizen engagement. Subjects and Methods: A mixed-method approach was applied. Quantitative data were collected from 400 citizens using Surabaya’s digital services, including licensing, e-health, and complaint systems. Qualitative data were gathered through interviews with 20 government officials, IT staff, and policymakers, complemented by document analysis of policy papers and smart city reports. This combination provided a comprehensive understanding of both service outcomes and internal bureaucratic dynamics. Results: Findings reveal significant improvements in service efficiency, with 78% of citizens reporting faster processing times and 70% expressing satisfaction with transparency. E-health and complaint management platforms strengthened trust and accountability. However, challenges persist, including digital literacy gaps among older citizens, limited internet access in peripheral areas, and bureaucratic resistance to innovation. Conclusions: Digital governance has accelerated Surabaya’s bureaucratic transformation by improving efficiency and trust. Sustaining progress requires continuous investment in digital infrastructure, inclusive access, and a supportive bureaucratic culture.